Statistical applications using fuzzy sets - Manton, Kenneth G. 1947-; Woodbury, Max A.; Tolley, H. D. (Wiley series in probability and mathematical statistics : Probability and mathematical statistics, 1994)
Now there's a third approach using a new strategy for resolving measure theoretic issues involving this type of data. That approach centers on the fuzzy set or fuzzy partition models generated by convex geometrical sets. Originally developed in electrical engineering, these models have been finding a growing number of applications in computer science, physics, and theoretical biology. This popularity stems from the power of fuzzy set models to vastly improve on the approximation of the infinite dimensionality and heterogeneity of the real world that arises from the use of statistical partitions, no matter how fine